Miranda Unchained:: The Evolution of Feminine Freedom in Screen Representations of The Tempest - Mora-Rioja, Arturo (International Journal of English Studies, 2025)
This paper examines the portrayal of female characters analogous to Miranda from William Shakespeare’s The Tempest in four audiovisual adaptations: the short black-and-white film The Tempest (Stow, 1908), the film Forbidden Planet (Wilcox, 1956), the episode “Requiem for Methuselah” from the TV series Star Trek (Bixby & Golden, 1969), and the Ikea TV commercial “Beds” (Cabral, 2014). Using gender theory alongside a semi-neo-historicist approach, my analysis contrasts the representation of these characters with the status of women’s rights in the corresponding historical periods. This study evaluates whether these portrayals reflect or challenge contemporaneous gender norms and societal roles and traces the broader evolution of gender equality and feminine freedom in the Western world from the 20th century to today. The findings suggest a generally positive trajectory, although often more progressive than that of the four productions’ historical realities.